Reversible Fluindione-Induced Chronic Interstitial Nephritis. (5th April 2016) - Crepin, Thomas; Bamoulid, Jamal; Courivaud, Cécile; Dahmani, Omar; Felix, Sophie; Ducloux, Didier
Abstract : Fluindione is well known to induce acute drug-induced interstitial nephritis (IN). Most cases occurred soon after the onset of treatment. We report a unique case of severe subacute fluindione-induced IN diagnosed 2 years after the treatment was begun. Renal function dramatically improved after fluindione withdrawal and steroid therapy.